Educational Robotics Public Policies Implementation Issues - Souza, Larissa Soares De; Maia, Claudia Juliette do N. A.; Dantas, Igor Matias De Lima; Melo, Rafael Cabral; Freitas, Marcus Vinícius Lima de; Oliveira, Denilton Silveira; Santana-Júnior, Orivaldo V.; Garcia, Luciane T. Dos Santos; Gonçalves, Luiz M. G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
We aim to analyze the implementation process of a public policy provided by a municipal law enacted for the provision of educational robotics as a complementary activity in the education network of Natal, RN, Brazil. From the perspective of educational robotics trainees (undergraduate students), we highlight the construction potential and the challenges faced out by them using an action research paradigm done in six school units of the municipal network. The performance of the monitors has been systematized in the period from late 2021 to 2024, from which we aim to understand the law implementation. Activity reports were produced with the actions developed in each school in the mentioned period, to carry out a reflective data analysis in accordance with the legal provisions in the municipal regulatory framework. Therefore, the main contribution of the article is the analysis carried out on the experiences of implementing RE as a public policy, which can be used or replicated in other basic level education networks in Brazil. This includes a possible methodology that can serve as a support for other similar projects abroad. Above all, we noticed that planning must be rigorous, and strictly followed, otherwise it will demotivate teachers and school students. Also, the interference of external actors such as monitors and teachers from Higher Education Institutions is another factor that we analyze as having a strong influence in the continuity of such initiative.